A review on electromagnetic microwave absorption properties: their materials and performance - Elmahaishi, Madiha Fathi; Azis, Raba'ah Syahidah; Ismail, Ismayadi; Muhammad, Farah Diana (Elsevier, 2022)
The elevated levels of electromagnetic (EM) radiation released by electronic instruments, communication devices, and information processing technologies are becoming a major concern nowadays. Consequently, great effort has been made to develop unique nanomaterials to enhance the electromagnetic absorption properties of microwave-absorbing materials. These materials should have superior reflection loss (RL), thin thickness, wide absorption bandwidth, low density, and light weightiness. This article discusses the electromagnetic microwave absorption basic theory, the materials and the performance will be highlighted. The strategies scheme to enhance the absorption properties of microwave absorbing materials (MAMs) will be elaborated. Metal-based composites often exhibit high efficiency to fulfill coveted magnetic and dielectric characteristics. This review provides a brief presentation of the useful theory of some selected microwave absorbers of ferrites and composites of carbon-based materials. In addition, the classifications of microwave absorbers according to important parameters for the fundamental microwave absorption property of the substance are discussed. The effect of great potential application in microwave absorbing materials (MAMs) with thin thicknesses was also investigated. Furthermore, this paper provides a comprehensive review study on several microwave absorption materials and their fundamental mechanisms of microwave absorption, dielectric loss, magnetic loss, dielectric/magnetic loss coupling, absorption bandwidth, and the reflection loss (RL) values of nanomaterials. The electromagnetic and microwave absorption properties of sandwich absorbers by the single- and double-layer microwave absorber, are studied intensively.